NaOCl effect on biofilm produced by Staphylococcus aureus isolated from the milking environment and mastitis infected cows - Melo, P. C. (2014)
Biofilms constitute a physical barrier, protecting the encased bacteria from detergents and sanitizers. The objective of this work was to analyze the effectiveness of sodium hypochlorite (NaOCl) against strains of Staphylococcus aureus isolated from raw milk of cows with subclinical mastitis and Staphylococcus aureus isolated from the milking environment (blowers and milk conducting tubes). The results revealed that, in the presence of NaOCl (150ppm), the number of adhered cells of the twelve S. aureus strains was significantly reduced. When the same strains were evaluated in biofilm condition, different results were obtained. It was found that, after a contact period of five minutes with NaOCl (150ppm), four strains (two strains from milk , one from the blowers and one from a conductive rubber) were still able to grow. Although with the increasing contact time between the bacteria and the NaOCl (150ppm), no growth was detected for any of the strains. Concerning the efficiency of NaOCl on total biofilm biomass formation by each S. aureus strain, a decrease was observed when these strains were in contact with 150 ppm NaOCl for a total period of 10 minutes. This study highlights the importance of a correct sanitation protocol of all the milk processing units which can indeed significantly reduce the presence of microorganisms, leading to a decrease of cow´s mastitis and milk contamination.